THE ROLE OF MULTICULTURAL LEARNING ENVIRONMENTS IN SHAPING STUDENTS’ MOTIVATION TO LEARN ENGLISH - Aminah Hasanah, Nur Afifah; Lestari , Wahyu; Zainuddin (Universitas Islam Ogan Komering Ilir Kayuagung, 2025)
This study examines the impact of multicultural learning environments on students’ motivation to learn English within the context of Sekolah Indonesia Kuala Lumpur (SIKL) in Malaysia. As a cross-cultural educational setting, SIKL serves as a unique space where diverse linguistic backgrounds, cultural identities, and social values converge, shaping students’ language learning experiences. Adopting a sociocultural perspective, this research examines how students’ interactions, cultural exchanges, and community practices contribute to their intrinsic and extrinsic motivation in English learning. Utilizing a qualitative case study approach, data were collected through classroom observations, interviews with students and teachers, and document analysis. The findings reveal that exposure to multiple cultures within the school environment fosters greater openness, communicative confidence, and positive attitudes toward English as a global language. Moreover, the presence of culturally responsive teaching practices and peer support systems significantly enhances students’ engagement and motivation. This study underscores the importance of acknowledging and integrating multicultural dynamics into language education to create more inclusive, motivating, and practical English learning experiences in international and Indonesian schools abroad.